การประยุกต์ใช้การวัดผลเชิงดุลยภาพ (Balanced scorecard) ในการบริหารจัดการงานห้องสมุดคณะรัฐศาสตร์ จุฬาลงกรณ์มหาวิทยาลัย - นฤมล กิจไพศาลรัตนา (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
"Using the balanced scorecard in Political Science Library, Chulalongkorn University" is a qualitative research. The objective of this study was to implement the balanced scorecard adopted from Robert S. Kaplan and David P. Norton in Political Science Library. The balanced scorecard examined the entire organization from four perspectives: the user perspective, the internal process perspective, the learning and growth perspective and the financial perspective. Each perspective had strategic objectives, goals and activities, associated with it. There were many implementation processes. First we analyzed the situations that called SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats). Next reviewed the library’s vision, mission and strategy map and clarified strategic objectives for each perspective. Then proposed the metrics that were specific, measurable, and balanced, analyzed the options for collecting the data and translated strategic issues into action plan. Benchmarking was chosen to measure and compare the work processes of our Library to 5 social and humanities sciences libraries in Chulalongkorn University: Faculty of Commerce and Accountancy Library. Faculty of Education Library, Faculty of Economics Library, Faculty of Law Library and Humanities information Center, Faculty of Arts. The results were then processed and summarized as follow:- 1. The vision of Political Science Library is:- non-profit organization and the leader in political science resources center in Thailand. 2. It’s missions are:- to satisfy the customers, provide deficiency information services, encourage the Library staffs and have social services responsibility. 3. In SWOT analysis, corporate strategy of Political Science Library is S-O strategy (Strengths and Opportunities) or matching approach and business strategy is to fulfill the Library into e-Library with high and efficiency technology.